2015
DOI: 10.1016/j.evalprogplan.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Applying national survey results for strategic planning and program improvement: The National Diabetes Education Program

Abstract: Since the 1970s, the federal government has spearheaded major national education programs to reduce the burden of chronic diseases in the United States. These prevention and disease management programs communicate critical information to the public, those affected by the disease, and health care providers. The National Diabetes Education Program (NDEP), the leading federal program on diabetes sponsored by the National Institutes of Health (NIH) and the Centers for Disease Control and Prevention (CDC), uses pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…The NDEP was initiated at a time when knowledge about diabetes was limited (30). The idea that an individual could act to manage his or her diabetes, prevent complications, and prevent or delay T2D was a relatively new concept for people with diabetes and their health care providers.…”
Section: Methodsmentioning
confidence: 99%
“…The NDEP was initiated at a time when knowledge about diabetes was limited (30). The idea that an individual could act to manage his or her diabetes, prevent complications, and prevent or delay T2D was a relatively new concept for people with diabetes and their health care providers.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted programs for early intervention and diabetes management for these high-risk groups are thus needed. Specific risk factors and possible barriers to adequate prevention and care of diabetes in selected ethnic groups can be more easily tackled learning from the experience accumulated in traditional immigration countries of Northern Europe [26e28], as well as in United States [29,30] and Canada [31], and from the work of colleagues operating in the geographical areas origin of the recent migratory flow toward Southern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies from different countries examined secular trends in lipid profiles [10][11][12][13][14][15][16]. One of them reported lifestyle factors contributing to such trends, including obesity, smoking, and alcohol drinking, but did not examine dietary factors [16]. Another study observed similar secular trends in serum cholesterol levels and dietary fat intake, but did not analyze their association [13].…”
Section: Introduction *mentioning
confidence: 99%